Precise GNSS Positioning with Time-differenced Carrier Phases at Variable Sampling Rates - S. Guo; H. Yang; Y. Gao (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Most Global Navigation Satellite System (GNSS) receivers typically have a sampling rate at 1Hz. However, variable sampling rates are required for optimal performance in different dynamic applications. For example, high sampling rates are crucial for precise tracking of high dynamic platforms such as unmanned aerial vehicle (UAV) navigation. Higher sampling rates help decrease positioning interval time and improve travel distance measurements especially when moving on a curvy route. On the contrary, lower sampling rates help saving power consumption and computation. Currently there is barely literature presenting the impact of sampling rates on positioning accuracy and what sampling rate is required for different vehicle dynamics considering the positioning accuracy and computational load. In this study, we extend TDCP to estimate position at different sampling rates and with high accuracy. We investigate and develop a GNSS software-defined radio (SDR) receiver to implement variable sampling-rate capability at low-cost. This approach provides flexibility, customization and scalability since the GNSS SDR can be reconfigured or updated via software to support multiple GNSS signals, systems or new techniques without requiring costly hardware modifications. The variable-rate phase observations from the GNSS SDR will be applied to form time-differenced carrier phase (TDCP) observations for precise positioning. The test results show that the GNSS-TDCP algorithm can achieve absolute precise positioning, but the positioning error will drift over time. Besides, the research results on the impact of different sampling rates on the positioning performance can help us to select an appropriate sampling rate for GNSS-TDCP system.